Role of interfaces in concrete proceedings of the international seminar held at the University of Dundee, Scotland, UK on 7th September 1999 - Dhir, Ravindra K.; Hewlett, P. C. (Creating with concrete., 1999)
This title deals with the role of interfaces in the prediction of durability and their effects on concrete characteristics and composite action.